2013
DOI: 10.17159/2413-3108/2013/v25i2a381
|View full text |Cite
|
Sign up to set email alerts
|

Exercise effects on mood in breast cancer patients

Abstract: Breast cancer is one of the most common cancers worldwide, and statistics reveal that the number of women diagnosed with breast cancer in South Africa is increasing. As such, medical practitioners will treat an increasing number of breast cancer patients. Although increasingly effective treatments improve patient survival intervals, a significant number of patients experience psychological distress, at the time of diagnosis and sometimes well beyond the start of treatment. This can be attributed to the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…The interviewed patients described how they dealt with the side effects of chemotherapy in a number of ways. The findings presented in the theme 'actively dealing with discomfort' are in line with those of a study carried out in South Africa 12 , which revealed that physical activity exerted a positive effect on mood and also alleviated symptoms of psychological distress in cancer patients. Furthermore, in our study, patients shared that they took supplementary drugs to reduce or prevent the impact of side effects; however, they did not appear to clearly understand what supplementary drugs they took or what effects they had.…”
Section: Discussionsupporting
confidence: 85%
“…The interviewed patients described how they dealt with the side effects of chemotherapy in a number of ways. The findings presented in the theme 'actively dealing with discomfort' are in line with those of a study carried out in South Africa 12 , which revealed that physical activity exerted a positive effect on mood and also alleviated symptoms of psychological distress in cancer patients. Furthermore, in our study, patients shared that they took supplementary drugs to reduce or prevent the impact of side effects; however, they did not appear to clearly understand what supplementary drugs they took or what effects they had.…”
Section: Discussionsupporting
confidence: 85%
“…While some studies have used exercise interventions where the main goal was fitness improvement and required access to facilities or equipment, other studies referred to different forms of physical exertion of moderate physical activity, such as home-based walking regimes or even occupational and household activities. 14 17 …”
Section: Methodsmentioning
confidence: 99%
“…It helps them to reduce specific side effects of treatment, for example, weakness and depressive symptoms, and it has been shown to increase survival rates and decrease the risk of cancer reappearance. 14 In fact, major health organisations recommend that cancer survivors should have at least 150 min of moderate-intensity or 75 min of high-intensity exercise combined with a minimum of two strengthening exercise sessions on a weekly basis. 6 …”
Section: Introductionmentioning
confidence: 99%
“… 7 However, physical activity is a non-pharmacologic, safe, feasible, and relatively low-cost alternative for depression management among women with breast cancer. 8 Increased physical activity levels may reduce depressive symptoms 9 and, thus, improve QoL throughout survivorship. 10 …”
Section: Introductionmentioning
confidence: 99%